What's the evidence? A review of current instruction and assessment in veterinary surgical education. Issue 5 (11th May 2022) - Simons, Micha C.; Hunt, Julie A.; Anderson, Stacy L.
Abstract: Veterinary surgical education is improved by studying the relevant literature. The aim of this literature review was to report the theory and methods used to provide surgical education to veterinary students; to discuss the training most likely to create a competent general practitioner; and to review assessment methods for simulated and live surgeries. The literature reviewed demonstrates that new graduates are expected to perform small animal sterilization, dental extraction, onychectomy, abscess treatment, aural hematoma repair, and mass removal with little or no supervision. Students require repetitive practice to reach competence; some practice can take place in a clinical skills laboratory on models or cadavers. When training novices, distributing practice over a longer time improves retention, but months without practice causes skills to decay. Suturing skills may be taught on models at a ratio of 1 instructor per 10 students. Veterinary students require 6‐10 repetitions of each small animal sterilization surgery to reach competence; however, learning curves for other surgeries have not been established. Assessment of surgical skills has been undertaken using objective structured clinical examinations (OSCEs) and observed model and live surgeries. Additional validated rubrics are needed in the field. Surgical educators are urged to continue to search for innovative ways to foster deliberate practice, assess skill, and provide feedback for students.